Effect of oxalic acid and sulphuric acid hydrolysis on the preparation and properties of pineapple pomace derived cellulose nanofibers and nanopapers - Neenu, K. V.; Dominic, C. D. Midhun; Begum, P. M. Sabura; Parameswaranpillai, Jyotishkumar; Kanoth, Bipinbal Parambath; David, Deepthi Anna; Sajadi, S. Mohammad; Dhanyasree, P.; Ajithkumar, T. G.; Badawi, Michael (International Journal of Biological Macromolecules, 2022)
Nanocellulose is the ``green magnet'' which attracts a wide spectrum of industries towards it due to its availability, biodegradability, and possible smart applications. For the first time, pineapple pomace was being explored as an economic precursor for cellulose nanofibers. Nanofiber isolation was accomplished using a chemo-mechanical method and solution casting was adopted for the development of nanopapers. Moreover, the study examines the structural, optical, crystalline, dimensional, and thermal features of nanofibers isolated using different acid hydrolysis (oxalic acid and sulphuric acid) methods. Fourier-transform infra-red spectroscopy, 13C solid-state nuclear magnetic resonance spectroscopy, and X-ray diffraction analysis indicated the presence of type I cellulose. The transmittance, crystallinity index, and thermal stability of PPNFS (sulphuric acid treated fiber) were greater than PPNFO (oxalic acid treated fiber). The transmission electron microscopy and dynamic light scattering analysis confirmed the nanodimension of PPNFO and PPNFS. While comparing the optical and mechanical properties of nanopapers, PPNFS outperforms PPNFO. The tensile strength of the prepared nanopapers (64 MPa (PPNFO) and 68 MPa (PPNFS)) was found to be high compared to similar works reported in the literature. The prepared nanopaper is proposed to be used for food packaging applications.
Keywords: cellulose nanofibers; Cellulosic nanopapers; Pineapple pomace